F aktor-Faktor yang Mempengaruhi Perhatian Konsumen terhadap Iklan di Internet - Deddy Chandra; Petra Surya Mega Wijaya (Jurnal Riset Manajemen dan Bisnis, 2009)
Facebook is a social networking website that is operated and privately owned by Faceboolc, Inc. The website has cttrrently more than 350 million active users with second position populrity worldwide ofier Google. More than 50?5 of Facebook users access their account daib. The website is free to users andit generates revenuefrom advertising, such as banner adt. Today, Facebook advertisernents become a reasonable optionfor mt ny cottp(mies on a smoll to giant scale as an ffictive media for publishing their promotion campaign. Facebook advertisernents hmte many different variables, ways, audierrces, and rnethods to mix their promotion campaigns thsn conventional prornotions do. A company, that wants to do online promotion oa Facebaok, needs to lonw which variables there are that influerrces Facebook user's attention beforethey do the promotion campaign This research is aimed a learning the effects of product, price, messoges, design, and layout on qdvertisement attention on the Facebookwebsite. The sampling was takenfrom college students who had had Facebook accountfor, at leost, 3 months and accessed their occount minimum 3 times a week.  The research result showed that generally, as a whole when using collective methods, all variables (product, price, messages, design, and layout)influenced advertisement attention on the Facebook website. In partial method, however, the result demonstroted that indivi&tally, product, and layout variables influenced the attention of the advertisements but price and design variables did not intluence advertisenents attention on the Facebook website.Kqruords: product, price, messages, desisrr, layout, Facebaok